Routledge handbook of the global history of warfare
1 online resource (xxiv, 530 pages).
Keywords: "This handbook examines key aspects of the development of the global history of warfare and the changing patterns of warfare over time. Although scholarship has long eschewed a chronological narrative of the evolution of warfare that privileges the Western experience, global histories of warfare have had difficulty avoiding an overemphasis on the West. The present volume is a collection of themes rather than a history per se; it provides important perspectives on the emergence of warfare as a global historical experience from the ancient past to the present-day. Drawing together numerous experts, it tells a broader, more inclusive story of the global, human experience with wars and warfare. The 35 essays are organized in eight thematic sections: Part I: Origins of Warfare Part II: Polities and Armed Forces in the Pre-modern Era Part III: Steppe Nomads of Eurasia Part IV: Naval Warfare and Piracy in the Pre-Industrial World Part V: The Impact of Gunpowder Part VI: Transition from Industrial to Total War Part VII: Wars of Decolonisation and Cold War Part VIII: Postmodern/New Wars These sections offer an overview of the global experience of warfare to help readers understand how the wars and the militaries we see today have been shaped by historical developments across the globe. This handbook will be of great interest to students of military history, naval history, strategic studies and world history in general"--